Knockdown of HMGB1 improves apoptosis and suppresses proliferation and invasion of glioma cells - Zhang, Jing; Liu, Cang; Hou, Ruiguang (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Background: The purposes of this study were to explore the effects of high mobility group protein box 1 (HMGB1) gene on the growth, proliferation, apoptosis, invasion, and metastasis of glioma cells, with an attempt to provide potential therapeutic targets for the treatment of glioma. Methods: The expressions of HMGB1 in glioma cells (U251, U-87MG and LN-18) and one control cell line (SVG p12) were detected by real time PCR and Western blotting, respectively. Then, the effects of HMGB1 on the biological behaviors of glioma cells were detected: the expression of HMGB1 in human glioma cell lines U251 and U-87MG were suppressed using RNAi technique, then the influences of HMGB1 on the viability, cycle, apoptosis, and invasion abilities of U251 and U-87MG cells were analyzed using in a Transwell invasion chamber. Also, the effects of HMGB1 on the expressions of cyclin D1, Bax, Bcl-2, and MMP 9 were detected. Results: As shown by real-time PCR and Western blotting, the expression of HMGB1 significantly increased in glioma cells (U251, U-87MG, and LN-18) in comparison with the control cell line (SVG p12); the vitality, proliferation and invasive capabilities of U251 and U-87MG cells in the HMGB1 siRNA-transfected group were significantly lower than those in the blank control group and negative control (NC) siRNA group (P